2021
DOI: 10.3389/ffgc.2021.657850
|View full text |Cite
|
Sign up to set email alerts
|

Bark Effects on Stemflow Chemistry in a Japanese Temperate Forest II. The Role of Bark Anatomical Features

Abstract: A fraction of rainfall drains to the soil surface down tree stems (as “stemflow”), and the resulting stemflow waters can be highly enriched with dissolved nutrients due to prolonged bark contact. To date, stemflow chemistry has been examined mostly in regards to the external morphology of the bark, while its relationship with bark anatomy has received little attention. Arguably, this represents a major knowledge gap, because bark anatomical traits are linked to the storage and transport of soluble (and insolub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…In addition to the morphometric characteristics of bark, its internal structure can play a significant role in affecting its water absorption capacity. In this investigation, it was suggested that the leaching rates of Mg 2+ and Ca 2+ may be influenced by the thickness of the rhytidome and periderm [30]. This study corroborated that Ca 2+ , along with Cl − , was more associated with the BWA% of the species that had a thicker bark texture (P. taeda).…”
Section: Discussionsupporting
confidence: 73%
“…In addition to the morphometric characteristics of bark, its internal structure can play a significant role in affecting its water absorption capacity. In this investigation, it was suggested that the leaching rates of Mg 2+ and Ca 2+ may be influenced by the thickness of the rhytidome and periderm [30]. This study corroborated that Ca 2+ , along with Cl − , was more associated with the BWA% of the species that had a thicker bark texture (P. taeda).…”
Section: Discussionsupporting
confidence: 73%
“…Coarse bark particles, the largest among the three categories, have a lower surface area compared to fine and medium particles, making them less susceptible to rapid moisture changes. The moisture content of coarse bark particles can range from about 10% to 40% [69].…”
Section: Physical Properties Of Bark Particleboard With Various Parti...mentioning
confidence: 99%
“…The moisture content of rough bark particles is lower than that of fine bark particles when wet. This is because rough bark particles have a smaller surface area but a larger volume, which restricts their capacity to absorb and retain moisture [69].…”
Section: MCmentioning
confidence: 99%
“…Some canopy traits may passively and indirectly influence solute concentrations, through the deposition of materials during dry periods (Saebø et al, 2012;Xu et al, 2019Xu et al, , 2020Oka et al, 2021a) and their subsequent wash-off and dilution during storms (Kazda, 1990;Van Stan et al, 2017;Xu et al, 2017). Other traits may directly modify the chemistry of throughfall and stemflow through physiological processes that uptake, leach, or transform soluble materials transported over plant organs during rainfall (Long et al, 1956;Tukey, 1966;Oka et al, 2021b). A less discussed but significant mechanism involves the exchange of solutes with resident animal and plant communities on the leaf and bark surfaces (Mabrouk et al, 2022).…”
Section: Why May Different Trees Release More Tension In Rainwater?mentioning
confidence: 99%
“…The exact physiological traits that may explain these uptake and leaching observations are currently unknown. A recent study examining various bark anatomical features and their relationship with lab-derived leachate chemical composition shed some insight, suggesting that K + concentration may be linked to the abundance of cellular structures associated with nutrient storage, like parenchyma (Oka et al, 2021b). The selective uptake of kosmotropic ions and leaching of chaotropic ions by canopies might affect the overall "structuring" of water and thereby its surface tension, which could in turn influence processes like water flow, absorption, and even evaporation rates.…”
Section: Why May Different Trees Release More Tension In Rainwater?mentioning
confidence: 99%